Anti-parasite behaviour of birds - Bush, Sarah E. (Philos Trans R Soc Lond B Biol Sci, 2018)
Birds have many kinds of internal and external parasites, including viruses, bacteria and fungi, as well as protozoa, helminths and arthropods. Because parasites have negative effects on host fitness, selection favours the evolution of anti-parasite defences, many of which involve behaviour. We provide a brief review of anti-parasite behaviours in birds, divided into five major categories: (i) body maintenance, (ii) nest maintenance, (iii) avoidance of parasitized prey, (iv) migration and (v) tolerance. We evaluate the adaptive significance of the different behaviours and note cases in which additional research is particularly needed. We briefly consider the interaction of different behaviours, such as sunning and preening, and how behavioural defences may interact with other forms of defence, such as immune responses. We conclude by suggesting some general questions that need to be addressed concerning the nature of anti-parasite behaviour in birds. This article is part of the Theo Murphy meeting issue ‘Evolution of pathogen and parasite avoidance behaviours’.